Efficient Construction of Volar Wrist Splints: A Biomechanical Study Comparing Splints of Different Material, Thickness, and Design. (September 2016) - Meals, Clifton; Castro, Nathan J.; Moss, David
Background: The aim was to test the null hypothesis that splint material, thickness, or longitudinal ridging does not affect the strength of a wrist splint.Methods: Ten splints were made according to each of 7 different splint designs (resulting in 7 groups of 10 splints each). All splints were the same length and were molded to approximate the contour of the volar hand, wrist, and forearm with the wrist in neutral. Three groups consisted of plaster splints of different thicknesses (8, 10, and 12 ply). Three additional groups included splints of the same thicknesses but with a longitudinal ridge. A single group was constructed from prefabricated fiberglass splinting material and did not involve a longitudinal ridge. Five splints in each group were subjected to 3-point bending mimicking flexion of the wrist and 5 were subjected to a 3-point bend mimicking wrist extension. Splints were loaded to failure using a servohydraulic load frame. Analysis of variance was used to compare splints.Results: Among the plaster splints, more layers of material and longitudinal ridging increased splint strength. Ridged 8-ply plaster splints exceeded the strength of nonridged 10-ply plaster splints. Ridged 8-ply plaster splints were similar in strength to fiberglass splints.Conclusions: The 8-ply ridged plaster splints may be a lighter, effective, and cheaper alternative to more common splint designs.